Partial agonists of dopamine receptors: theoretical principles of combining antipsychotics including partial agonists to treat schizophrenia. (March 2023) - Cookson, John; Pimm, Jonathan; Brentnall, Andrew
SUMMARY: Partial agonists such as aripiprazole are often used in addition to a full antagonist such as amisulpride, risperidone or olanzapine in an attempt to mitigate side-effects such as sedation, hyperprolactinaemia and weight gain. However, there can be unintended consequences, including worsening of psychosis. Moreover, previous exposure to a partial agonist may impair the subsequent response to a potent antipsychotic such as haloperidol used to control symptoms of relapse. To understand the mechanisms involved, a method is needed to compare potency in the pharmacological effects of different drugs used in combinations. This article is intended to explore and explain the theoretical principles based on the dopamine hypothesis of schizophrenia. We apply the method to analyse a recently described trial in which two full antagonists (olanzapine and amisulpride) are compared individually and in combination.